Analisis kepercayaan diri siswa sekolah dasar dalam pembelajaran Pendidikan Pancasila - Yulianti; Afrensia R. Jola Pedi; Didik Iswahyudi (COLLASE (Creative of Learning Students Elementary Education), 2026)
Self-confidence is an important aspect of the development of elementary school students, particularly in Pancasila education. This study aims to analyze the level of self-confidence of fourth-grade students at SDN Gadang 4, Malang City, as well as the role of teachers in fostering self-confidence during the learning process. The research employed a qualitative approach with a case study method. Data were collected through observations and questionnaires administered to 58 fourth-grade students (classes 4A and 4B), as well as in-depth interviews with the Pancasila Education teacher on the topic “Application of Pancasila Values.” The results indicate that students’ levels of self-confidence vary, with 10 students (17.24%) having high self-confidence, 13 students (22.42%) at a moderate level, and 35 students (60.34%) exhibiting low self-confidence. Some students were able to complete tasks independently, confidently express their opinions, and demonstrate a positive self-concept. However, others still felt hesitant, afraid of making mistakes, insecure, inexperienced, afraid of criticism, lacking family support, and influenced by peer pressure. These findings emphasize the crucial role of teachers in providing positive encouragement, fostering independence, strengthening self-concept, and delivering learning that is relevant to students’ experiences. The study recommends using active learning methods, providing positive reinforcement, and creating a safe and enjoyable classroom environment to optimize the development of students’ self-confidence.